Formaldehyde release from root-canal sealers: influence of method - Koch, Martin Jean (International endodontic journal, 1999)
To examine formaldehyde release from three different root-canal sealers: one phenol resin, one epoxy resin and one paraformaldehyde containing zinc oxide eugenol cement.